Clinical significance of CD8(+) and FoxP3(+) tumor-infiltrating lymphocytes and MFG-E8 expression in lower rectal cancer with preoperative chemoradiotherapy - Harada, Yuzo (Mol Clin Oncol, 2021)
Preoperative chemoradiotherapy (CRT) for rectal cancer contributes to tumor down-staging and decreases locoregional recurrence. However, each patient shows a significantly different response to CRT. Therefore, the identification of predictive factors to CRT response would be beneficial to avoid unnecessary treatment. Cancer immunity in patients has been suggested to play an important role in the eradication of the tumor by CRT. In the present study, the utility of CD8(+) and forkhead box P3 (FoxP3)(+) tumor-infiltrating lymphocytes (TILs) and the expression of a novel immuno-regulatory factor, lactadherin (MFG-E8), in predicting CRT effectiveness in patients with rectal cancer was examined. A total of 61 patients with rectal cancer, who underwent curative resection following CRT were included in the study. The numbers of CD8(+) and FoxP3(+) TILs in a biopsy taken before CRT and MFG-E8 expression level in the specimens obtained at the time of the surgery after CRT were examined using immunohistochemical staining, and their association with clinicopathological characteristics, including patient survival, was determined. The tumors with more CD8(+) TILs in the biopsy samples before CRT showed a significantly more favorable CRT response. The patients with tumors and a higher number of CD8(+) TILs before CRT also exhibited significantly longer disease-free and overall survival times. Higher MFG-E8 expression level in post-CRT specimens was significantly associated with favorable CRT response; however, no significant association was found with any other clinicopathological characteristics, including survival time. The number of CD8(+) TILs before CRT was a valuable predictor for CRT response and was associated with favorable prognosis in patients with lower rectal cancer and who were treated with CRT. High MFG-E8 expression level after CRT was also associated with a favorable CRT response.